The Educational Importance of the Organization of Reading Classes in the Primary Classes with the Help of New Advanced Pedagogical Technologies - Ergasheva Durdona Safarali kizi (Research Parks Publishing LLC, 2022)
In the current globalisation era, proper and purposeful use of modern technology is necessary. This article describes the terminology of Technology Development, comments on pedagogical technology and the effective use of pedagogical technologies in primary classes.